Seed morphology of Portulaca (Portulacaceae) in Cuba and taxonomic implications - García-Beltrán, José Angel; Barrios, Duniel; Bécquer, Eldis R.; Arias, Salvador (Phytotaxa, 2021)
Portulaca is the only genus in Portulacaceae and includes ca. 115 species with worldwide distribution. 12 species (one naturalized) occur in Cuba. The taxonomic value of seeds characters for the circumscription of species, by comparing macro- and micromorphological characters, is analyzed. The seeds of Cuban purslanes do not present association patterns between types of undulations of the anticline walls. The relief of their periclinal walls allows the corroborate certain variation in the distribution range of some species. The delimitation of Portulaca species in Cuba using seeds characters, provided as an identification key and descriptions, confirms the taxonomic value of such characters and strengthens the circumscriptions supported by the rest of the plant structures. This is largely given by the standardization of macromorphological terms with a micromorphological basis, the color of the mature seeds and their dimensions.